Correlation Between Waist Hip Ratio (RLPP) and Hypertension at Sudiang Raya Health Center in Makassar City - Rusydi, Hanina Nur Zahra; Kanang, Indah Lestari Daeng; Fattah, Nurfachanti; Nurmadilla, Nesyana; Tahir, Akina Maulidhany (Jurnal Biologi Tropis, 2024)
Elevated blood pressure is the hallmark of hypertension, a dangerous illness that raises the risk of heart disease, stroke, and other illnesses. Globally, the prevalence of hypertension reaches 29.2%, with higher prevalence in some regions, such as in South Sulawesi which reaches 27.61%. One of the main risk factors for hypertension is central obesity, which can be measured using the Waist-Hip Circumference Ratio (RLPP). RLPP is more effective than Body Mass Index (BMI) in measuring visceral fat accumulation that is associated with increased blood pressure. This accumulation of fat in the abdominal area can increase vascular resistance and cause metabolic disturbances that contribute to hypertension. This study aimed to determine the correlation between Waist-Hip Ratio (RLPP) and hypertension at Sudiang Raya Health Center, Makassar.  This study combined a total sampling strategy with a cross-sectional approach. 89 hypertensive patients who satisfied the inclusion requirements made up the study sample. The Stasistical Program for Social Science (SPSS) was used to evaluate the collected data. The result showed that the majority of hypertensive patients were female (61.8%) with an age group of 55-64 years (49.4%), and 61.8% had RLPP reflecting cental obesity. Statistical analysis showed a significant correlation between RLPP and hypertension (p=0.000). The conclusion of this study is that there is a significant correlation between Waist-Hip Ratio (RLPP) and the incidence of hypertension at Sudiang Raya Health Center, Makassar.